2020
DOI: 10.3390/ijerph17093238
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Three-Day Bamboo Forest Therapy Session on the Physiological Responses of University Students

Abstract: Studies have indicated that natural environments have the potential to improve the relationship between a stressful life and psychological well-being and physical health. Forest therapy has recently received widespread attention as a novel solution for stress recovery and health promotion. Bamboo is an important forest type in many countries, especially in East and Southeast Asia and in African countries. Bamboo is widespread throughout southwestern China. Empirical field research on the physiological effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 46 publications
1
77
0
Order By: Relevance
“…The benefits of the proximity to green areas highlight that creativity somehow has a relationship with well-being. In those spaces, creativity can occur in a relaxed manner, [ 10 , 71 , 72 ] for instance when people take breaks, go for walks and interact with others, and not necessarily during working hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of the proximity to green areas highlight that creativity somehow has a relationship with well-being. In those spaces, creativity can occur in a relaxed manner, [ 10 , 71 , 72 ] for instance when people take breaks, go for walks and interact with others, and not necessarily during working hours.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars such as Whyte [ 65 ], Dober [ 66 , 67 ], Strange and Banning [ 68 , 69 ], Kenney et al [ 70 ], Hajrasouliha [ 33 , 34 ], Wood and Dovey [ 14 ], Francis et al [ 10 ] Lau and Yang [ 71 ] and Zeng et al [ 72 ] suggest that the following characteristics of the built environment must be considered in the planning and design of successful knowledgescapes: For the organization of urban functions, a campus has to provide a mix of sports, research, residential and various academic activities. Public spaces are reinforced by the appropriate proximity of buildings (density) and the juxtaposition of activities that complement one another (diversity).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this category, 3 articles were included,[ 14 16 17 ] which corresponds to 33% of the number of articles analyzed. In this category, it was noticed that the integral provision of social, medical, and health services are considered enhancers for improvement in quality of life, since they act as interdisciplinary proposals of care and HP.…”
Section: Methodsmentioning
confidence: 99%
“…The main lifestyle modification observed in the studies is the incentive to combat sedentary lifestyle through walking in the. Their association was observed with a pleasant scenario for participants, such as forests and forests in China[ 14 ] and South Korea. [ 17 ] In this sense, the following benefits were evidenced: reduction of heart rate and blood pressure, increase in oxygen saturation, management of situations of coping with stress, reduction of depressive signs.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on architecture, urban design, campus design and planning such as 'flexible spaces' (Whyte 1980), 'life between buildings' (Gehl 2011;Gehl and Svarre 2013), 'physical features' and 'urban design qualities' (Ewing and Clemente 2013;Ewing et al 2016), 'landscape taxonomy' (Dober 1992;Mehta 2019), and 'post-occupancy evaluation (POE) for outdoor spaces' (Göçer et al 2018) have shown that the location of built environment features can structurally and aesthetically support peoples' behaviour and perceptions in public spaces. For this research, the relational pair of the built environment and perceived affordances of creativity at campuses was based on campus design literature (Dober 1992(Dober , 2014Strange et al, 2001;Strange and Banning 2015;Kenney et al, 2005;Hajrasouliha 2017;Lau and Yang 2009;Zeng et al 2020).…”
Section: Location Of Built Environment Featuresmentioning
confidence: 99%